A Role for Accumbal Glycine Receptors in Modulation of Dopamine Release by the Glycine Transporter-1 Inhibitor Org25935 - Höifödt Lidö, Helga; Ericson, Mia; Marston, Hugh; Söderpalm, Bo (Frontiers in Psychiatry, 2011)
Abstract Accumbal glycine modulates basal and ethanol-induced dopamine levels in the nucleus accumbens (nAc) as well as voluntary ethanol consumption. Also, systemic administration of the glycine transporter-1 inhibitor Org25935 elevates dopamine levels in nAc, prevents a further ethanol-induced dopamine elevation and robustly and dose-dependently decreases ethanol consumption in rats. Here we investigated whether Org25935 applied locally in nAc modulates dopamine release, and whether accumbal glycine receptors or NMDA receptors are involved in this tentative effect. We also addressed whether Org25935 and ethanol applied locally in nAc interact with dopamine levels, as seen after systemic administration. We used in vivo microdialysis coupled to HPLC-ED in freely moving male Wistar rats to monitor dopamine output in nAc after local perfusion of Org25935 alone, with ethanol, or Org25935-perfusion after pre-treatment with the glycine receptor antagonist strychnine or the NMDA receptor glycine site antagonist L-701.324. Local Org25935 increased extracellular dopamine levels in a subpopulation of rats. Local strychnine, but not systemic L-701.324, antagonized the dopamine-activating effect of Org25935. Ethanol failed to induce a dopamine overflow in the subpopulation responding to Org25935 with a dopamine elevation. The study supports a role for accumbal glycine receptors rather than NMDA receptor signaling in the dopamine-activating effect of Org25935. The results further indicate that the previously reported systemic Org25935-ethanol interaction with regard to accumbal dopamine is localized to the nAc. This adds to the growing evidence for the glycine receptor as an important player in the dopamine reward circuitry and in ethanol’s effects within this system.